Effects of Landscape Age and Salinity on Plant Community Composition and Productivity in Opportunistic and Constructed Wetlands in the Athabasca Oil Sands Region, Alberta ... - Mombourquette, Ashlee Dawn (Graduate Studies, 2023)
Wetlands comprise 65% of the Athabasca Oil Sands Region (AOSR) surface mineable area and thus support diverse flora (approximately 400 species in Alberta). Due to increased anthropogenic land disturbance activities such as bitumen extraction, reclamation of surface mineable areas will also increase. The resulting reclaimed areas will tend to be sodium-enriched compared to pre-disturbance landscapes. In this thesis, forty young (<40 years old) stratified-randomly selected wetlands were sampled on reclaimed landscapes at Syncrude’s Mildred Lake lease and from reference wetlands in adjacent areas in the AOSR to determine how salinity and age influence the vegetation community composition, and the biomass of six dominant wetland plant species (Carex aquatilis, Calamagrostis canadensis, Carex atherodes, Carex utriculata, Schoenoplectus tabernaemontani, and Typha latifolia) found on reclaimed and reference landscapes. Wetland vegetation communities on reclaimed landscapes differed from those on reference ...